Strategies for Supporting and Building Student Resilience in Canadian Secondary and Post-Secondary Educational Institutions - Brenda Gamble; Daniel Crouse (Ital Publication, 2020)
Communication, problem-solving skills, emotional intelligence, and mental health and well-being are key characteristics of a resilient student. These skills are also needed to navigate increasingly complex life and work environments in the 21st century. In addition, resilient students are dedicated to learning, are focused on academic success, and are better equipped to adapt to change and the evolving workplace. An interdisciplinary team from both secondary and post-secondary educational institutions situated at Ontario Tech University, Oshawa, Canada have collaborated to develop and implement strategies and curricula to support and enhance student resilience. The Mental Health Commission of Canada recommends "increase collaboration between (these) institutions - sharing best practices and processes for effective strategy development, and implementation" to better support student reliance and the successful transition from secondary to post-secondary education.  We present the overall rationale and approach taken to support capacity building for student resilience in post-secondary institutions.  As well as highlighting specific curricula and virtual strategies implemented (e.g., Graphic Novel, Mandalas, Resiliency Handbook) to engage students in building and maintaining resilience.